ACCIDENT ALERT IN PIN DROP AREAS MORADABAD INSTITUTE OF TECHNOLOGY - Agarwal, Anurag; Singh, Isha; Gupta, Sugandh; *, Ankit; Yadav, Kusum; Rajpoot, Yogesh (IJRDO - Journal of Social Science and Humanities Research, 2017)
This project is developed for the users to have accident alert in modern traffic system. This device can be used in highly accidental area and pin drop curves to avoid accidents. In India there are so many curve areas like Nainital, Haridwar etc. Due to random curves it is very difficult to determine that at which speed we should drive, usually people think they have experience so they drive at high speed just to save their time. They do not know, that vehicle from the opposite side is coming at which speed? as a result accident takes place. This project help to avoid accidents in these types of areas and it will help to track the location of vehicle as well.